The Highlander's bride trouble - Wine, Mary (Sourcebooks Casablanca, 2014)
Raised by her father and brother, Nareen Grant is strong, confident, well-educated-- and skilled with a bow and dagger. It's a tumultuous time for Scotland, and events conspire against her. Betrayed by her family, she makes her way alone, until she lands in the lap of Saer MacLeod. But she wants no help from a savage man of the Isles.